Determination of the Parameters of Langmuir-Type Isotherms by the Frontal Analysis Method. Some Identification Aspects - Waldemar Nowicki; Grażyna Nowicka (Adsorption Science & Technology, 2005)
The applicability of the classical frontal analysis method for the estimation of the parameters of various Langmuirian-type adsorption isotherms was examined. Elution profiles corresponding to several adsorption models were simulated using the equilibrium/dispersive model of chromatography. A noise sequence was added to the calculated profiles to simulate the detector error, following which the isotherm parameters were derived back from the generated chromatograms. The uncertainty of the estimates is discussed critically in terms of the standard deviations from the mean and real values of the parameters.